SEGMENTATION OF THE TARGET AUDIENCE AS AN ELEMENT OF STRATEGIC PLANNING OF MARKETING ACTIVITY IN SOCIAL MEDIA - KOVALENKO, Nataliia; MALAKHOVA, Yuliia; HORDIEIEV, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The rapidly developing modern world is characterized by dynamic changes in all spheres of life, in particular in marketing and communications. The Internet and social media have become an integral part of the daily lives of millions of people, creating new business opportunities and changing traditional approaches to consumer awareness. The use of social media has become one of the key tools in building relationships between companies and their customers, as well as in creating and maintaining brand awareness. The article examines the mechanisms and principles of strategic planning of marketing activity in social media. Modern social platforms have become an integral part of the business environment, and their effective use allows companies to increase brand awareness, attract new customers and maintain long-term relationships with existing audiences. Special attention is paid to the analysis of the target audience, market segmentation, the selection of appropriate social platforms and the development of a content strategy.An important element of a successful marketing strategy is a personalized approach to consumers based on demographic, behavioral and psychographic characteristics. This allows companies to more effectively communicate their messages to their target audience and achieve their marketing goals. The article provides examples of successful use of social media in the field of insurance services, in particular, emphasizes the importance of collecting data on customer behavior and implementing analytical tools to improve the effectiveness of marketing campaigns.It also examines the benefits and risks of using social media in the context of building brand trust, personalizing content, and increasing customer engagement. The results of the study emphasize the need for constant data analysis and adaptation of the marketing strategy in order to achieve better results and increase competitiveness in the market.The object of the study is the process of strategic planning of marketing activity in social media, in particular the segmentation of the target audience and its influence on the effectiveness of marketing campaigns.Research methods. The following traditional general scientific methods are the methodological basis: systematic, logical approaches, induction and deduction, systematization and classification, grouping, descriptive and comparative methods, the method of synthesis and analysis, tabular method. Such special methods as market analysis and customer segmentation are also used.
Keywords: Social Media; Strategic Planning; Marketing; Target Audience; Segmentation; Content Strategy; Analytics; Insurance Services